2019
DOI: 10.1371/journal.pone.0218681
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasitic infections and associated factors in children of three rural schools in Colombia. A cross-sectional study

Abstract: Rural children are one of the populations that are most vulnerable to gastrointestinal parasite infections. Such diseases decrease the quality of life and result in growth and cognitive delays in the long term. This cross-sectional study was conducted to determine the frequency of intestinal parasite infections among rural schoolchildren in the municipality of Apulo, Colombia. A total of 97 stool samples from children aged between 5 and 15 years were collected and examined via direct light microscopy. Microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 45 publications
4
61
0
3
Order By: Relevance
“…Diarrhea sufferers in this phase have experienced a phase called dysentery. The occurrence of diarrhea can be mild or severe levels [19,20]. Oxiuris vermicularis is the most common worm parasite infecting humans.…”
Section: Resultsmentioning
confidence: 99%
“…Diarrhea sufferers in this phase have experienced a phase called dysentery. The occurrence of diarrhea can be mild or severe levels [19,20]. Oxiuris vermicularis is the most common worm parasite infecting humans.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies of these protozoan pathogens have been conducted in Colombia. Studies of samples from indigenous communities in the Amazon (Sánchez et al, 2017), from a rural region in La Vírgen (Ramírez et al, 2015), and from children in rural schools in the municipality of Apulo (Hernández et al, 2019), Cundinamarca, found G. intestinalis in human fecal samples. Sub-assemblages AI, AII, BIII and BIV and sub-assemblages AII, BIII and BIV were detected in the feces of children in nurseries of the Colombian Institute of Family Welfare.…”
Section: Discussionmentioning
confidence: 99%
“…The highly prevalent intestinal helmints have been reported as Ascaris lumbricoides, Trichuris trichiura, Necator americanus, Ancylostoma duodenale and Strongyloides stercoralis, intestinal protozoa as Blastocystis sp., G. duodenalis, Dientamoeba fragilis and Entamoeba spp. [5,9].…”
Section: Introductionmentioning
confidence: 99%